CuO:Se composite films and its photovoltaic application. (December 2022) - Gao, Rongrong; Hua, Xiaodong; Gao, Fei; Yang, Zhou; Li, Jiahui; Zhang, Chaoqun; Hodes, Gary; Liu, Shengzhong (Frank)
Abstract: Cupric oxide (CuO) and selenium (Se) are old photoelectric materials, and their photovoltaic properties have always received attention. However, CuO has a high melting point (1026 ℃) and will decompose near its melting point, so it is difficult to prepare high crystallinity CuO films. Selenium (Se) can not efficiently absorb sunlight because of its large optical band gap (1.9 eV). Here, a CuO:Se composite film was prepared by radio frequency magnetron co-sputtering of CuO and Se and low temperature annealing (200 ℃). The experimental results show that this composite material film has the advantages of CuO and Se, and overcome their disadvantages. It has strong absorption of light in the entire solar spectral range (250–2500 nm, average absorptance ∼80 %). A prototype solar cell based on this composite film was fabricated and its power conversion efficiency (PCE) is up to 2.05 %, which is much higher than that of the pure CuO (0.007 %) or pure Se (1.05 %) film solar cells. This material should be promising for photovoltaic and other photo-electrical devices application. Graphical Abstract: ga1